Implementasi Algoritme Trivium Stream Cipher Dan Shamir's Secret Sharing Pada File Portable Document Format (PDF) - Muhammad Wahyu Rizqi Pratama; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Securing data in the form of files by encrypting the files is one way to secure data in the concept of cryptography, so that other people who are not entitled to find files that are private or confidential. In this study implementing data security using two cryptographic algorithms namely Trivium Stream Cipher and Shamir's Secret Sharing. Both algorithms are applied to a *.pdf format document file. * .pdf document file format is a file format that is widely used when sending files because it can be distributed on any computer with the same look. But with the development of technology, the security of this file also weakens like tapping or losing. Therefore we need a method that can improve the security of this * .pdf format document file. It is expected that by combining these two algorithms can improve security in * .pdf format files. From the testing that has been carried out this system requires an average execution time of 2.363 seconds for a file size of 15 Kb, 6.384 seconds for a file size of 31 Kb and 12.456 seconds for a file of size 40 Kb.